Effect of Mango Leaf Shoot Extract (Mangifera indica L.) on Zebrafish (Danio rerio) Cell Regeneration Induced by Hyperglicemia - Adisty Virakawugi Darniwa; Tri Cahyanto; Siti Nurul Hidayah (Universitas Negeri Malang, 2021)
Abstract. In many cases, diabetics often have difficulty in wound healing and lead to amputation. Hyperglycemia is an early symptom of diabetic which is characterized by high blood glucose levels. Cell regeneration is one of part by wound healing process. Mango plants have benefits as medicinal plants because they have secondary metabolites that can help heal wounds. The purpose of this study was to determine the effect of mango leaf shoot extract on blood glucose levels of zebrafish (Danio rerio) hyperglycemia due to alloxan and glucose induction and role of mango leaf shoot extract on zebrafish caudal fin regeneration. This study used an experimental method with 5 group treatments: control group, hyperglycemia, metformin 0,75 w/v, extract 10 µg/ml and extract 20 µg/ml. Parameters observed include blood glucose level, fin length and survival rate. Hyperglycemia was measured by blood glucose level, caudal fin regeneration was analayzed using fin length, also environmental factors and survival rate were measured. Result showed that mango leaf shoot extract 20 µg/ml was efective in reducing blood glucose levels, reaching 68,31% and aproaching metformin 0,75 w/v treatment with a decrease in blood glucose levels reaching 70,1%. Mango leaf shoot extract with concentration 20 µg/ml significantly different (p < 0,05) from hyperglycemia group and extract 10 µg/ml. Extract 20 µg/ml was effective in assisting the regeneration process with an increase caudal fin length reaching 0.94 cm during the treatment period.